Adsorption of Sr2+ by MCM-41 Functionalized by Aminosilane Group - H Faghihian; Sh Nasri; S Khansari (مجله علوم و فنون هسته‌ای, 2011)
In this research, MCM-41 molecular sieve was synthesized, and was characterized by XRD, FT-IR, TG and BET techniques. The ability of the adsorbent towards Sr2+ was then investigated. In order to increase the adsorption capacity of the molecular sieve, the sample was modified by 3-amino propyltrimethoxysilane. The modified MCM-41 was used for the Sr2+ removal at different experimental conditions. The effect of different parameters including pH of the solution, contact time, initial concentration of Sr2+ and temperature were also studied. We concluded that the adsorption of Sr2+ increases as the initial pH of the solution increases. The maximum adsorption capacity of 6.0 mg/g obtained.